National Surveillance of Methicillin-Resistant Staphylococcus aureus Bloodstream Infections in Canadian Acute-Care Hospitals. (October 2020) - Pelude, Linda; Campbell, Jennifer; Bakai-Anderson, Suzanne; Bedard, Pat; Comeau, Jeannette; Durand, Joan; Embil, John; Embree, Joanne; Evans, Gerald; Frenette, Charles; Ivany, Allana; Katz, Kevin; et al.
Abstract : Background: Bloodstream infections (BSIs) due to methicillin-resistant Staphylococcus aureus (MRSA) are important causes of morbidity and mortality in hospitalized patients. Long-term national MRSA BSI surveillance establishes rates for internal and external comparison and provide insight into epidemiologic, molecular, and resistance trends. Here, we present and discuss National MRSA BSI incidence rates and trends over time in Canadian acute-care hospitals from 2008 to 2018. Methods: The Canadian Nosocomial Infection Surveillance Programme (CNISP) is a collaborative effort of the Association of Medical Microbiology and Infectious Disease Canada and the Public Health Agency of Canada. Since 1995, the CNISP has conducted hospital-based sentinel surveillance of MRSA BSIs. Data were collected using standardized definitions and forms from hospitals that participate in the CNISP (48 hospitals in 2008 to 62 hospitals in 2018). For each MRSA BSI identiﬁed, the medical record was reviewed for clinical and demographic information and when possible, 1 blood-culture isolate per patient was submitted to a central laboratory for further molecular characterization and susceptibility testing. Results: From 2008 to 2013, MRSA BSI rates per 10, 000 patient days were relatively stable (0.60–0.56). Since 2014, MRSA BSI rates have gradually increased from 0.66 to 1.05 in 2018. Although healthcare-associated (HA) MRSA BSI has shown a minimal increase (0.40 in 2014 to 0.51 in 2018), community-acquired (CA) MRSA BSI has increased by 150%, from 0.20 in 2014 to 0.50 in 2018 (Fig. 1). Laboratory characterization revealed that the proportion of isolates identified as CMRSA 2 (USA 100) decreased each year, from 39% in 2015 to 28% in 2018, while CMRSA 10 (USA 300) has increased from 41% to 47%. Susceptibility testing shows a decrease in clindamycin resistance from 82% in 2013 to 41% in 2018. Conclusions: Over the last decade, ongoing prospective MRSA BSI surveillance has shown relatively stable HA-MRSA rates, while CA-MRSA BSI rates have risen substantially. The proportion of isolates most commonly associated with HA-MRSA BSI (CMRSA2/USA 100) are decreasing and, given that resistance trends are tied to the prevalence of specific epidemic types, a large decrease in clindamycin resistance has been observed. MRSA BSI surveillance has shown a changing pattern in the epidemiology and laboratory characterization of MRSA BSI. The addition of hospitals in later years that may have had higher rates of CA-MRSA BSI could be a confounding factor. Continued comprehensive national surveillance will provide valuable information to address the challenges of infection prevention and control of MRSA BSI in hospitals. Funding: None Disclosures: None